Most Consumers Don't Buy Hybrids: Is Rational Choice a Sufficient Explanation?. Issue 1 (19th December 2018) - Duncan, Denvil; Ku, Arthur Lin; Julian, Alyssa; Carley, Sanya; Siddiki, Saba; Zirogiannis, Nikolaos; Graham, John D.
Abstract : Although federal regulation of vehicle fuel economy is often seen as environmental policy, over 70% of the estimated benefits of the 2017–2025 federal standards are savings in consumer expenditures on gasoline. Rational-choice economists question the counting of these benefits since studies show that the fuel efficiency of a car is reflected in its price at sale and resale. We contribute to this debate by exploring why most consumers in the United States do not purchase a proven fuel-saving innovation: the hybrid-electric vehicle (HEV). A database of 110 vehicle pairs is assembled where a consumer can choose a hybrid or gasoline version of virtually the same vehicle. Few choose the HEV. A total cost of ownership model is used to estimate payback periods for the price premiums associated with the HEV choice. In a majority of cases, a rational-choice explanation is sufficient to understand consumer disinterest in the HEV. However, in a significant minority of cases, a rational-choice explanation is not readily apparent, even when non-pecuniary attributes (e.g., performance and cargo space) are considered. Future research should examine, from a behavioral economics perspective, why consumers do not choose HEVs when pricing and payback periods appear to be favorable.